Long-Term Monitoring of Carbon Dynamics and Mangrove Health Using Remote Sensing: A Study of Balikpapan Bay, Indonesia - A. A. Md. Ananda Putra Suardana; Nanin Anggraini; Nugraheni Setyaningrum; Muhammad Rizki Nandika; Azura Ulfa; Devica Natalia Br Ginting; Kuncoro Teguh Setiawan; Ratih Dewanti Dimyati (Marine Science Department Diponegoro University, 2026)
Mangrove ecosystems provide critical ecological services, including supporting coastal fisheries, protecting shorelines, and functioning as significant carbon sinks within the global carbon cycle. These ecosystems play a substantial role in climate change mitigation, as they are capable of sequestering up to three times more carbon dioxide (CO₂) than terrestrial forests. Given increasing anthropogenic pressures and environmental change, continuous monitoring of mangrove health is essential to sustain these ecological functions and ecosystem services. Remote sensing technology offers a cost-effective and efficient approach for large-scale assessment, spatial analysis, and long-term monitoring of mangrove conditions. This study utilized cloud-free Landsat-8 imagery from 2013 to 2020 to evaluate mangrove health in Balikpapan Bay using the Mangrove Health Index (MHI), which classifies conditions into three categories: excellent, moderate, and poor. Carbon storage was estimated using a model integrating vegetation indices with Above-Ground Carbon (AGC). The results revealed a fluctuating yet overall positive trend in mangrove health, with the “excellent” category increasing by 1.023% (174.78 ha), while the “poor” category decreased by 1.098% (187.67 ha) over the study period. AGC values exhibited a comparable pattern, reaching a peak of 375.54 Mg.ha-1 in 2018 (mean: 125.85 Mg.ha-1). A strong positive correlation (r = 0.994) was observed between estimated mangrove health and AGC values, indicating that healthier mangrove ecosystems possess greater carbon sequestration potential. These findings highlight the importance of sustained monitoring and adaptive management strategies to support mangrove conservation and strengthen their contribution to climate change mitigation at regional and landscape management and policy scales.